Paste composition and semiconductor device

The paste composition with controlled shrinkage and thermal expansion properties addresses the reliability and heat dissipation issues of conventional bonding materials, ensuring effective thermal conductivity and adhesive strength for semiconductor elements.

JP7617932B2Active Publication Date: 2025-01-20KYOCERA CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022545598
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-31
Filing Date
2021-08-04
Publication Date
2025-01-20
Estimated Expiration
2041-08-04

AI Technical Summary

Technical Problem

Conventional bonding materials like solder and silver paste fail to provide adequate reliability and heat dissipation under high temperatures, necessitating a more effective bonding method for semiconductor elements that can operate efficiently at elevated temperatures.

Method used

A paste composition comprising silver particles, a thermosetting resin, a curing agent, and a solvent, with a controlled shrinkage rate of 15% or less, which enhances thermal conductivity and adhesive properties by optimizing the ratio of silver particles and resin content, and includes hollow silver particles with controlled porosity and thermal expansion properties.

Benefits of technology

The composition achieves low thermal resistance and high thermal conductivity, improving bonding strength and reducing voids, thereby enhancing the reliability and performance of semiconductor devices under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617932000002
    Figure 0007617932000002
  • Figure 0007617932000003
    Figure 0007617932000003
  • Figure 0007617932000001
    Figure 0007617932000001
Patent Text Reader

Abstract

This paste composition comprises (A) silver particles, (B) a thermosetting resin, (C) a curing agent, and (D) a solvent, wherein the shrinkage rate of the paste composition after curing is at most 15%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a paste composition and a semiconductor device. [Background technology]

[0002] In recent years, the efficiency of semiconductor elements has been improved, and the heat generated by semiconductor elements has increased, leading to an increase in the operating temperature. In addition, a bonding material is required to have reliability and heat dissipation properties at high temperatures. Candidates for bonding materials include solder and silver paste, which have been used in the past. However, these are insufficient in terms of reliability and heat dissipation properties at high temperatures, and a bonding method suitable for high-temperature operation is desired. In order to meet this demand, a silver sintering paste using silver nanoparticles that can be bonded at low temperatures and have excellent thermal and electrical conductivity has attracted attention. For example, Patent Document 1 discloses a silver paint composition (silver sintering paste) containing silver nanoparticles whose surfaces are coated with a specific protective agent. In addition, Patent Document 2 discloses a silver sintering paste containing a silver-containing powder (silver nanoparticles) whose surfaces are coated with a specific surfactant. In addition, Patent Document 3 discloses a silver paste containing an aggregate of silver fine particles having an average primary particle diameter of 40 nm to 130 nm, which shows good dispersibility in a desired dispersion solvent by changing the surface properties of the silver fine particles.

[0003] Silver sintering paste using silver nanoparticles has excellent thermal and electrical conductivity because it is heated to harden and shrink the resin it contains, bringing adjacent silver or silver compound particles into contact with each other or fusing the contacting parts. When the thermosetting resin contained in the silver sintering paste is cured and the silver particles are sintered, the paste tends to shrink in volume due to contraction caused by the curing of the thermosetting resin and the volume of the silver nanoparticles being reduced due to the separation of protective groups from the silver nanoparticle surfaces. For example, Patent Document 3 discloses that the shrinkage rate of a bonding material using the aggregated particles after pre-drying is in the range of 26% to 62%. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-142173 A [Patent Document 2] International Publication No. 2006 / 057348 [Patent Document 3] JP 2017-101264 A Summary of the Invention

[0005] That is, the present disclosure relates to the following: [1] A paste composition comprising (A) silver particles, (B) a thermosetting resin, (C) a curing agent, and (D) a solvent, the paste composition having a shrinkage rate after curing of 15% or less. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a cross-sectional view illustrating a schematic diagram of (A1) silver particles when the (A1) silver particles according to the present disclosure are hollow particles. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of (A1) silver particles after sintering when the (A1) silver particles according to the present disclosure are hollow particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, the present disclosure will be described in detail with reference to one embodiment.

[0008] <Paste composition> The paste composition of the present disclosure comprises (A) silver particles, (B) a thermosetting resin, (C) a curing agent, and (D) a solvent, and has a shrinkage rate after curing of 15% or less. As described above, the silver sintering paste tends to shrink significantly due to a combination of the hardening shrinkage of the thermosetting resin and the volumetric shrinkage of the silver nanoparticles. At this time, the silver particles fuse (neck) with adjacent silver particles and sinter so as to aggregate toward the center of the paste composition. This results in thermal conductivity. Therefore, the greater the amount of silver nanoparticles, the greater the shrinkage of the paste composition after hardening, and the higher the thermal conductivity. In reaction to this, the silver particles become sparse at the bonding interface with the element or element support member to be bonded, and the ratio of the thermosetting resin increases in proportion to this. As a result, the bonding strength with the element or element support member is improved. However, the thermal resistance of the bonding interface with the element or element support member to be bonded increases. The paste composition of the present disclosure has a shrinkage rate of 15% or less after curing, and therefore has good adhesive properties, low thermal resistance at the bonding interface, and excellent thermal conductivity and electrical conductivity.

[0009] If the shrinkage rate after curing of the paste composition (curing shrinkage rate) exceeds 15%, there is a risk that the thermal resistance of the bonding interface will be large when the paste composition is used to bond a substrate and a semiconductor element. From this viewpoint, the curing shrinkage rate may be 12% or less, or may be 10% or less. Thus, if the curing shrinkage rate is 15% or less, the thermal resistance of the bonding interface of an electronic component using the paste composition can be reduced even when bonded without pressure. Furthermore, the reduced thermal resistance allows the thermal conductivity to be maintained even if the amount of silver particles is reduced. As a result, it is possible to relatively increase the amount of thermosetting resin, and the adhesive strength is improved. Furthermore, by using the paste composition of the present disclosure, the thermal resistance can be reduced compared to conventional products, making it possible to reduce the content of (A) silver particles. In addition, by reducing the content of (A) silver particles, it becomes possible to reduce the amount of (D) solvent. In particular, voids are reduced when bonding large-area chips.

[0010] The cure shrinkage rate can be adjusted by appropriately selecting (A) the type of silver particles, (B) the type of thermosetting resin, and (D) the type and content of the solvent. The cure shrinkage can be calculated, for example, by measuring the film thickness (μm) of the paste composition before and after curing using a micrometer and using the following formula. Specifically, it can be measured by the method described in the examples. Curing shrinkage rate (%) = paste film thickness after curing / paste film thickness before curing × 100

[0011] [(A) Silver particles] The (A) silver particles used in the present disclosure are not particularly limited, but from the viewpoint of reducing the cure shrinkage rate of the paste composition, the silver particles may comprise at least one type selected from (A1) silver particles which are secondary agglomerate particles having an average particle diameter of 0.5 μm or more and 2.0 μm or less, formed by agglomeration of particles including primary particles with an average particle diameter of 10 nm or more and 100 nm or less, and (A2) silver particles which are secondary agglomerate particles having an average particle diameter of more than 2.0 μm and not more than 15.0 μm, formed by agglomeration of particles including primary particles with an average particle diameter of more than 100 nm and not more than 500 nm. The shape of the (A) silver particles is not particularly limited and may be, for example, spherical, flake-like, etc. The shape of the (A) silver particles may be spherical.

[0012] The average particle size of the primary particles of the (A) silver particles can be measured as follows, specifically, by the method described in the Examples. Silver particles are embedded in epoxy resin at 60°C for 120 minutes. Cross-section milling is performed using an ion milling device at an acceleration voltage of 6 kV, processing mode C3 (±30°), and processing time of 30 minutes. The cross-section of the obtained spherical silver particles is observed using a field emission scanning electron microscope (FE-SEM) at an acceleration voltage of 1.0 kV and a magnification of 10,000 to 200,000 times to measure the circle equivalent diameter of 200 silver particles. The measured circle equivalent diameter of the 200 silver particles is processed using image analysis software and calculated by number averaging.

[0013] The average particle diameter of the secondary agglomerate particles of the (A) silver particles is the particle diameter at which the cumulative volume becomes 50% in the particle size distribution measured using a laser diffraction particle size distribution measuring device (50% particle diameter D 50Specifically, it can be measured by the method described in the Examples.

[0014] [(A1) Silver particles] The (A1) silver particles are secondary agglomerated particles having an average particle size of 0.5 μm or more and 2.0 μm or less, which are formed by agglomerating particles containing primary particles having an average particle size of 10 nm or more and 100 nm or less. The (A1) silver particles may be spherical. If the average particle size of the primary particles is 10 nm or more, the specific surface area is not too large, and the workability of the paste composition can be improved, and if it is 100 nm or less, the sinterability is improved. From this viewpoint, the average particle size of the primary particles may be 10 nm or more and 50 nm or less, or 20 nm or more and 50 nm or less. In addition, when the average particle size of the secondary agglomerate particles is 0.5 μm or more, the storage stability is improved, and when it is 2.0 μm or less, the sinterability is good. From this viewpoint, the average particle size of the secondary agglomerate particles may be 1.0 μm or more and 2.0 μm or less.

[0015] The (A1) silver particles may be hollow particles. Here, hollow particles refer to particles having voids inside. When the (A1) silver particles are hollow particles, the (A1) silver particles have an outer shell formed by particles including aggregated primary particles, and voids present inside the outer shell. The voids may be present in the center of the (A1) silver particles. Such hollow particles become hollow inside during the process of aggregation and densification of silver particles obtained by reducing a copper compound as shown in the synthesis examples. The (A1) silver particles may have a porosity of 20% or more and 50% or less before sintering and a porosity of 30% or more and 60% or less after sintering. Furthermore, the shell thickness before sintering may be 0.05 μm or more and 0.5 μm or less, the shell thickness after sintering may be 0.05 μm or more and 0.4 μm or less, and the rate of change in the shell thickness due to sintering may be 15% or more and 50% or less. When the porosity before sintering, the porosity after sintering, the shell thickness before sintering, the shell thickness after sintering, and the change rate of the shell thickness due to sintering are each within the above range, the inside of the highly active silver particles is sintered first during sintering, so that the volumetric shrinkage of the paste composition is small, and the cure shrinkage rate of the paste composition can be reduced. In addition, since sintering progresses mainly on the inside of the highly active silver particles, the porosity after sintering is larger than the porosity before sintering. Furthermore, when the porosity before sintering, the porosity after sintering, the shell thickness before sintering, the shell thickness after sintering, and the change rate of the shell thickness due to sintering are each within the above range, the (A1) silver particles have a positive thermal expansion coefficient between 150 and 300 ° C., as described below. From the viewpoint of reducing the cure shrinkage rate of the paste composition, the porosity of the (A1) silver particles before sintering may be 20% or more and 40% or less. The porosity of the (A1) silver particles after sintering may be 30% or more and 50% or less. The outer shell thickness of the (A1) silver particles before sintering may be 0.22 μm or more and 0.42 μm or less. The outer shell thickness of the (A1) silver particles after sintering may be 0.18 μm or more and 0.35 μm or less. The rate of change in the outer shell thickness due to sintering of the (A1) silver particles may be 20% or more and 50% or less.

[0016] In the present disclosure, the porosity and shell thickness after sintering of the (A1) silver particles are measured using the (A1) silver particles sintered under conditions of a nitrogen atmosphere at a sintering temperature of 175 to 225°C for a sintering time of 1 to 3 hours. For example, the (A1) silver particles may be sintered under conditions of a nitrogen atmosphere at a temperature of 190°C for 2 hours. The porosity and shell thickness of the (A1) silver particles before sintering can be adjusted to within the above ranges by appropriately adjusting the average particle size of the primary particles of the (A1) silver particles, and the porosity and shell thickness of the (A1) silver particles after sintering can be adjusted to within the above ranges by optimizing the average particle size of the primary particles of the (A1) silver particles and the sintering temperature within the above ranges.

[0017] The porosity is determined by observing the cross-section of the (A1) silver particle cut with an ion milling device using a field emission scanning electron microscope (FE-SEM), and calculating the cross-sectional area (μm2) of the pores contained in the entire silver particle in the field of view. 2 ) (total cross-sectional area of ​​the voids), and the cross-sectional area of ​​all silver particles in the field of view (μm 2 ) (total cross-sectional area), and can be specifically measured by the method described in the Examples. Porosity (%) = total cross-sectional area of ​​pores / total cross-sectional area × 100 (1)

[0018] The rate of change in the thickness of the outer shell due to sintering is defined by the following formula (2), and specifically, can be measured by the method described in the Examples. The shell thicknesses before and after sintering are measured for 200 silver particles by observing the cross sections of (A1) silver particles cut with an ion milling device using a field emission scanning electron microscope (FE-SEM). The shell thicknesses of the measured 200 silver particles are processed using image analysis software and then averaged by number. Change in shell thickness due to sintering (%) = (T A -T B ) / T A ×100 (2) (In the formula, T A is the shell thickness before sintering (μm), and T B is the shell thickness (μm) after sintering under the above sintering conditions.

[0019] The (A1) silver particles may further have a positive thermal expansion coefficient in the firing temperature range of 150 to 300° C. The thermal expansion coefficient of the (A1) silver particles may be 0.2 ppm / ° C. or more and 10.0 ppm / ° C. or less, or may be 1.5 ppm / ° C. or more and 8.0 ppm / ° C. or less. In the present disclosure, the thermal expansion coefficient of (A1) silver particles is measured by applying a load of 200 kgf to Ag powder silver particles for 1 minute using a mini hydraulic press (Specac) to create a cylindrical pellet-shaped sample with a diameter of 5 mm and a thickness of 1 mm, and then measuring the thermal expansion of the obtained sample using a thermomechanical analyzer (TMA) (Seiko Instruments Inc., product name: TMA SS150) under conditions of heating from room temperature (25°C) to 350°C at a heating rate of 20°C / min. The thermal expansion coefficient based on the pellet length at 25°C is then determined as the thermal expansion coefficient in the firing temperature range of 150 to 300°C.

[0020] The sintering start temperature of silver particles having a positive linear expansion coefficient is the timing at which contraction starts, that is, the temperature at which the thermal expansion coefficient becomes maximum, and is usually in the range of 150 to 300°C.

[0021] When the temperature at which the thermal expansion coefficient is shown is within this range, the shells of the silver particles expand during sintering of the paste composition, increasing the opportunities for contact between the silver particles themselves and between the silver particles and the bonding surface, improving the thermal conductivity with the bonding surface and reducing the thermal resistance. As a result, even if the content of (A) silver particles is relatively small, better thermal resistance than before can be obtained. Since good thermal resistance can be obtained even if the content of (A) silver particles is kept low, it is possible to reduce the amount of dilution solvent. By reducing the amount of dilution solvent, a bonding surface with fewer voids can be obtained, resulting in good thermal conductivity and thermal resistance. The mechanism by which (A1) silver particles have a positive linear expansion coefficient is not clear, but the present inventors have speculated as follows based on the observation of silver particles upon heating: Fig. 1 is a cross-sectional view typically showing (A1) silver particles in the present disclosure when the (A1) silver particles are hollow particles, and Fig. 2 is a cross-sectional view typically showing (A1) silver particles after sintering. As shown in Fig. 1, secondary agglomerate particles 10 having an outer shell 1 formed by agglomerating particles including primary particles with an average particle diameter of 10 nm or more and 100 nm or less and voids 2 present inside the outer shell 1 tend to undergo necking on the outer side 4 of the outer shell 1 compared to the inner side 3 of the outer shell 1, resulting in a large specific surface area of ​​the inner surface of the outer shell 1. In other words, the ratio of the inner circumference to the outer circumference of the (A1) silver particles is large. In secondary agglomerate particles 10 having such voids 2, the inner side 3 of the outer shell is expanded during sintering, which exerts a force that spreads the particles outward. Therefore, it is presumed that the thickness of the outer shell 1 of secondary agglomerate particles 10 is thin and the secondary agglomerate particles have a positive linear expansion coefficient, as shown in Fig. 2.

[0022] The (A1) silver particles may further have organic protective molecules attached thereto. Examples of the organic protective molecules include carboxylic acids, amines, amides, etc. The organic protective molecules may be carboxylic acids from the viewpoint of improving the dispersibility of the (A1) silver particles.

[0023] The amount of organic protective molecules attached to the total amount of the (A1) silver particles may be 0.15 mass % or more and 3.0 mass % or less, or 0.5 mass % or more and 3.0 mass % or less, or 1.3 mass % or more and 3.0 mass % or less, from the viewpoints of low-temperature sintering properties and storage stability. The amount of the attached organic protective molecule can be determined from the amount of mass loss of the (A1) silver particles when heated from 230° C. to 320° C. using a thermogravimetric and differential thermal analyzer (TG-DTA). Specifically, it can be measured by the method described in the Examples.

[0024] The (A1) silver particles may be produced by the following method.

[0025] (A1) Method for producing silver particles (A1) A method for producing silver particles includes, for example, a step of adding ammonia water to an aqueous solution containing a silver compound to obtain a silver ammine complex solution, and a step of reducing the silver ammine complex in the silver ammine complex solution obtained in the above step with a reducing compound to obtain a silver particle-containing slurry.

[0026] (Step of Obtaining Silver Ammine Complex Solution) In this step, aqueous ammonia is added to an aqueous solution containing a silver compound to obtain a silver ammine complex solution. Examples of the silver compound include silver nitrate, silver chloride, silver acetate, silver oxalate, silver oxide, etc. From the viewpoint of solubility in water, the silver compound may be silver nitrate or silver acetate.

[0027] From the viewpoint of controlling the average particle size (primary particle size) of the primary particles of (A1) silver particles within the above-mentioned ranges, and from the viewpoint of controlling the porosity before sintering, the porosity after sintering, the outer shell thickness before sintering, the outer shell thickness after sintering, and the rate of change in the outer shell thickness due to sintering within the above-mentioned ranges, the amount of ammonia blended may be 2 mol or more and 50 mol or less, or 5 mol or more and 5 mol or less, or 10 mol or more and 50 mol or less, per mol of silver in the aqueous solution containing the silver compound. When the amount of ammonia added is 2 mol or more per mol of silver, the primary particle size and the porosity do not become too small, and when it is 50 mol or less per mol of silver, the primary particle size and the porosity do not become too large. In the present disclosure, the present inventors presume that when the (A1) silver particles are hollow particles, the hollow particles are formed by reducing a silver ammine complex at a low temperature, whereby the nitrogen-containing compound diffuses into the precipitated silver particles, and the precipitated silver particles diffuse inward to form weak aggregates, forming a hollow structure inside the silver particles. Therefore, the hollow particles do not necessarily have a completely closed space, but have a structure that is approximately spherical and has a space in the center.

[0028] (Step of obtaining silver particle-containing slurry) In this step, the silver ammine complex in the silver ammine complex solution obtained in the previous step is reduced with a reducing compound to obtain a silver particle-containing slurry.

[0029] By appropriately adjusting the amount of silver in the silver ammine complex and the content of the reducing compound, the aggregation of the primary particles can be controlled, and the average particle size of the resulting secondary aggregate particles can be set within the above-mentioned range.

[0030] The reducing compound is not particularly limited as long as it has the reducing power to reduce the silver ammine complex and deposit silver. The redox potential of the reducing compound may be 1 V or more. Examples of such reducing compounds include hydrazine derivatives. By using a hydrazine derivative having a strong reducing power as the reducing compound, the primary particles of the silver particles in the silver ammine complex tend to aggregate to form secondary aggregated particles having a void in the center. Examples of hydrazine derivatives include hydrazine monohydrate, methylhydrazine, ethylhydrazine, n-propylhydrazine, i-propylhydrazine, n-butylhydrazine, i-butylhydrazine, sec-butylhydrazine, t-butylhydrazine, n-pentylhydrazine, i-pentylhydrazine, neo-pentylhydrazine, t-pentylhydrazine, n-hexylhydrazine, i-hexylhydrazine, n-heptylhydrazine, n-octylhydrazine, n-nonylhydrazine, n-decylhydrazine, n-undecylhydrazine, n-dodecylhydrazine, cyclohexylhydrazine, phenylhydrazine, 4-methylphenylhydrazine, benzylhydrazine, 2-phenylethylhydrazine, 2-hydrazinoethanol, acetohydrazine, etc. These may be used alone or in combination of two or more. The hydrazine derivative has a strong reducing power, and therefore fine silver particles having high crystallinity and orientation can be obtained.

[0031] From the viewpoint of controlling the primary particle size within the above ranges, and from the viewpoint of controlling the porosity before sintering, the porosity after sintering, the shell thickness before sintering, the shell thickness after sintering, and the rate of change in the shell thickness due to sintering within the above ranges, the amount of the reducing compound may be 0.25 mol or more and 20.0 mol or less, or 0.25 mol or more and 10.0 mol or less, or 1.0 mol or more and 5.0 mol or less per mol of silver in the silver ammine complex. When the content of the reducing compound is 0.25 mol or more per mol of silver in the silver ammine complex, the primary particle size and the porosity do not become too small, and when it is 20 mol or less, the primary particle size and the porosity do not become too large.

[0032] Furthermore, the temperature of the silver ammine complex solution when reducing the silver ammine complex may be less than 30°C, or may be 0°C or more and less than 20°C, or may be 0°C or more and less than 10°C. If the temperature of the silver ammine complex solution is within this range, the aggregation of the primary particles is controlled, and the average particle size of the obtained secondary aggregate particles is within the above-mentioned range. The secondary aggregate particles can have a desired hollow structure by reducing the silver compound at a relatively low temperature using a hydrazine derivative with strong reducing power.

[0033] (A process for attaching organic protective molecules to silver particles) The (A1) method for producing silver particles may further include, after the step of obtaining a silver particle-containing slurry, a step of adding organic protective molecules to the silver particle-containing slurry obtained in the above step, thereby causing the organic protective molecules to adhere to the silver particles. Examples of the organic protective molecule include carboxylic acid, amine, amide, etc. From the viewpoint of improving dispersibility, the organic protective molecule may be carboxylic acid. Examples of carboxylic acids include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, caprylic acid, octylic acid, nonanoic acid, capric acid, oleic acid, stearic acid, and isostearic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and diglycolic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, and gallic acid; and hydroxy acids such as glycolic acid, lactic acid, tartronic acid, malic acid, glyceric acid, hydroxybutyric acid, tartaric acid, citric acid, and isocitric acid.

[0034] The amount of organic protective molecules may be 1 mmol or more and 20 mmol or less, or 1 mmol or more and 10 mmol or less, or 1 mmol or more and 5 mmol or less, relative to 1 mol of silver particles, from the viewpoint of controlling the primary particle size within the above-mentioned ranges and controlling the porosity before sintering, the porosity after sintering, the outer shell thickness before sintering, the outer shell thickness after sintering, and the rate of change in the outer shell thickness due to sintering within the above-mentioned ranges. When the amount of organic protective molecules is 1 mmol or more, the primary particle size and the porosity do not become too small, and when the amount of organic protective molecules is 20 mmol or less, the primary particle size and the porosity do not become too large.

[0035] [(A2) Silver particles] The (A2) silver particles are secondary agglomerated particles having an average particle diameter of more than 2.0 μm and not more than 15.0 μm, which are formed by agglomerating particles including primary particles having an average particle diameter of more than 100 nm and not more than 500 nm. If the average particle diameter of the primary particles exceeds 100 nm, the specific surface area is not too large, and the workability of the paste composition can be improved, and if it is 500 nm or less, the sinterability is improved. From this viewpoint, the average particle diameter of the primary particles may be 150 nm or more and 500 nm or less, or 200 nm or more and 400 nm or less. In addition, when the average particle diameter of the secondary agglomerate particles exceeds 2.0 μm, the specific surface area is not too large and the viscosity of the paste composition is appropriate, and when it is 15.0 μm or less, the occurrence of bleeding of the paste composition is controlled, and the paste composition can be made to have good dispensability, and both can improve workability. From this viewpoint, the average particle diameter of the secondary agglomerate particles may be 3.0 μm or more and 15.0 μm or less, or 3.0 μm or more and 12.0 μm or less.

[0036] The (A2) silver particles may be solid particles, where solid particles refer to particles that have substantially no space inside.

[0037] The (A2) silver particles may be produced by the same method as the (A1) silver particles, by obtaining a silver ammine complex solution, adding a reducing compound to reduce the silver ammine complex in the solution. Furthermore, after reducing the silver ammine complex, organic protective molecules may be added to the obtained silver particle-containing slurry to attach the organic protective molecules to the silver particles. Specifically, the (A2) silver particles may be produced by the method described in the Examples.

[0038] The reducing agent is not particularly limited, but for example, solid particles can be easily formed by using sodium borohydride, lithium aluminum hydride, etc. These may be used alone or in combination of two or more kinds.

[0039] In producing the (A2) silver particles, the average particle size of the primary particles and the average particle size of the secondary aggregate particles can be controlled within the above-mentioned ranges by appropriately adjusting the amount of silver in the silver ammine complex, the amount of ammonia used, the amount of reducing agent, and the amount of organic protective molecule. The amount of ammonia to be added may be 2 mol or more and 50 mol or less, 5 mol or more and 50 mol or less, or 10 mol or more and 50 mol or less, per 1 mol of silver in the aqueous solution containing the silver compound. The amount of the reducing agent to be added may be 0.25 mol or more and 20 mol or less, 0.25 mol or more and 10 mol or less, or 1 mol or more and 5 mol or less, per 1 mol of silver in the silver ammine complex. The amount of the organic protective molecule may be 1 mmol or more and 20 mmol or less, or 1 mmol or more and 10 mmol or less, or 1 mmol or more and 5 mmol or less, per 1 mol of silver particles.

[0040] The total content of the (A1) silver particles and the (A2) silver particles in the (A) silver particles may be 40% by mass or more and 100% by mass or less, or may be 50% by mass or more and 100% by mass or less, from the viewpoint of reducing the cure shrinkage rate of the paste composition.

[0041] In the present disclosure, the (A) silver particles may contain silver particles other than the (A1) silver particles and the (A2) silver particles. When the (A) silver particles contain silver particles other than the (A1) silver particles and the (A2) silver particles, the content of such silver particles may be 60 mass % or less, or may be 50 mass % or less, based on the total amount of the (A) silver particles.

[0042] The tap density of the (A) silver particles is 0.5 g / cm from the viewpoint of dispersibility. 3 More than 7.0g / cm 3 or less than 2.0 g / cm 3 More than 7.0g / cm 3 or less, 4.0 g / cm 3 More than 7.0g / cm 3 It may be less than 4.5 g / cm 3 More than 7.0g / cm 3 It may be less than 4.5 g / cm 3 More than 6.5g / cm 3 The tap density of the (A) silver particles can be measured using a tap density meter in accordance with ASTM standard test method B 527, and specifically, can be measured by the method described in the examples.

[0043] The (A) silver particles have a specific surface area, as determined by the BET method, of 0.5 m from the viewpoint of sinterability. 2 / g or more, 2.5m 2 / g or less, and 2 / g or more, 1.5m 2 / g or less, and 2 / g or more, 1.2m 2 / g or less, and 2 / g or more, 1.2m 2 / g or less. The specific surface area of ​​the (A) silver particles can be measured by a BET single-point method using nitrogen adsorption with a specific surface area measuring device, and specifically, it can be measured by the method described in the Examples.

[0044] The content of the (A) silver particles may be 70% by mass or more and 98% by mass or less, or 75% by mass or more and 95% by mass or less, based on the total amount of the paste composition. When the (A) silver particles content is 70% by mass or more, the thermal conductivity can be improved, and when it is 95% by mass or less, the adhesive strength can be improved.

[0045] [(B) Thermosetting resin] The thermosetting resin (B) used in the present disclosure is not particularly limited as long as it has a positive cure shrinkage rate, but from the viewpoint of adhesive strength when heated, it may be a flexible epoxy resin that is liquid at room temperature (25°C) (hereinafter, also referred to as a liquid flexible epoxy resin). In addition, by using a flexible epoxy resin as the thermosetting resin (B), the cure shrinkage rate of the paste composition can be reduced. For purposes of this disclosure, a flexible epoxy resin refers to an epoxy resin that, when cured with a stoichiometric amount of diethylenetriamine ("DETA"), has a durometer hardness of 30 or less using a Type D durometer, or a cured elastic modulus of 2 GPa or less.

[0046] The liquid flexible epoxy resin is not particularly limited as long as it has two or more epoxy groups in one molecule and exhibits flexibility, and examples of the liquid flexible epoxy resin include diglycidyl ether of polyethylene glycol, diglycidyl ether of polypropylene glycol, polyglycidyl ether of long-chain polyol including polyoxyalkylene glycol or polytetramethylene ether glycol containing an alkylene group having 2 to 9 carbon atoms (or 2 to 4 carbon atoms); copolymer of glycidyl (meth)acrylate with a radical polymerizable monomer such as ethylene, vinyl acetate, or (meth)acrylic acid ester. Examples of such resins include copolymers, (co)polymers of conjugated diene compounds or (co)polymers of partially hydrogenated conjugated diene compounds in which unsaturated carbon bonds have been epoxidized, polyester resins having epoxy groups, urethane-modified epoxy resins having urethane bonds or polycaprolactone bonds introduced therein, polycaprolactone-modified epoxy resins, dimer acid-modified epoxy resins having epoxy groups introduced into the molecules of dimer acid or its derivatives, and rubber-modified epoxy resins having epoxy groups introduced into the molecules of rubber components such as nitrile rubber (NBR), carboxy-terminated butadiene nitrile rubber (CTBN), polybutadiene, and acrylic rubber. These may be used alone or in combination of two or more.

[0047] The durometer hardness of the liquid flexible epoxy resin after curing may be 10 or more and 30 or less, measured by a type D durometer, from the viewpoint of reducing voids at the bonding interface.

[0048] The elastic modulus of the liquid flexible epoxy resin after curing may be 1 GPa or less, or 0.5 GPa or less, from the viewpoint of reducing voids at the bonding interface. The elastic modulus can be measured by a dynamic viscoelasticity measuring device, specifically, by the method described in the examples.

[0049] The epoxy equivalent of the liquid flexible epoxy resin may be 200 or more and 2000 or less, or 300 or more and 1800 or less, from the viewpoint of reducing the cure shrinkage rate of the paste composition.

[0050] Specific examples of the liquid flexible epoxy resin include YX7105 (manufactured by Mitsubishi Chemical Corporation, product name), YX7110 (manufactured by Mitsubishi Chemical Corporation, product name), YL7410 (manufactured by Mitsubishi Chemical Corporation, product name), EP-4003S (manufactured by ADEKA Corporation, product name), EP-4000S (manufactured by ADEKA Corporation, product name), TSR-960 (manufactured by DIC Corporation, product name), TSR-601 (manufactured by DIC Corporation, product name), Examples of such products include EXA-4850-150 (manufactured by DIC Corporation, product name), EXA-4850-1000 (manufactured by DIC Corporation, product name), EXA-4816 (manufactured by DIC Corporation, product name), EXA-4822 (manufactured by DIC Corporation, product name), BPO-20E (manufactured by New Japan Chemical Co., Ltd., product name), and BEO-60E (manufactured by New Japan Chemical Co., Ltd., product name).

[0051] From the viewpoint of a balance between adhesiveness and thermal conductivity, the blending amount of the (B) thermosetting resin may be 1 mass % or more and 20 mass % or less, or may be 2 mass % or more and 15 mass % or less, based on the total amount of the paste composition.

[0052] [(C) Hardener] The (C) curing agent used in the present disclosure is not particularly limited as long as it is used as a curing agent for the (B) thermosetting resin. Examples of the (C) curing agent include phenolic resins, dicyandiamide, amine compounds, latent amine compounds, cationic compounds, acid anhydrides, and special epoxy curing agents. These may be used alone or in combination of two or more.

[0053] The (C) curing agent may be (C1) a phenol resin from the viewpoint of heat resistance, or (C2) dicyandiamide from the viewpoint of adhesive strength under heat. Examples of the (C1) phenolic resin include bisphenols such as bisphenol F, bisphenol A, bisphenol S, tetramethyl bisphenol A, tetramethyl bisphenol F, tetramethyl bisphenol S, dihydroxydiphenyl ether, dihydroxybenzophenone, tetramethyl biphenol, ethylidene bisphenol, methyl ethylidene bis(methylphenol), cyclohexylidene bisphenol, and biphenol, and derivatives thereof; trifunctional phenols such as tri(hydroxyphenyl)methane and tri(hydroxyphenyl)ethane, and derivatives thereof; compounds obtained by reacting phenols such as phenol novolac and cresol novolac with formaldehyde, which are mainly binuclear or trinuclear, and derivatives thereof. These may be used alone or in combination of two or more. The blending amount of the (C1) phenol resin may be 1 part by mass or more and 100 parts by mass or less, or 1 part by mass or more and 50 parts by mass or less, per 100 parts by mass of the (B) thermosetting resin.

[0054] An example of a commercially available product of the (C2) dicyandiamide is DICY-7 (trade name, manufactured by Japan Epoxy Resins Co., Ltd.). The blending amount of the (C2) dicyandiamide may be 0.5 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the (B) thermosetting resin.

[0055] From the viewpoint of curability and adhesiveness, the (C) curing agent may be used in combination with (C1) a phenol resin and (C2) dicyandiamide. When the (C1) phenolic resin and (C2) dicyandiamide are used in combination as the (C) curing agent, the blending amount of the (C1) phenolic resin may be 1 part by mass or more and 10 parts by mass or less, or 2 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the (B) thermosetting resin. Also, the blending amount of the (C2) dicyandiamide may be 0.5 parts by mass or more and 5 parts by mass or less, or 0.6 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the (B) thermosetting resin.

[0056] The mass ratio of the (C1) phenol resin to the (C2) dicyandiamide [(C1):(C2)] may be from 1:1 to 10:1, or from 1:1 to 8:1.

[0057] The blending amount of the (C) curing agent may be 0.5 or more and 1.5 or less equivalents in terms of equivalent ratio to the (B) thermosetting resin, from the viewpoint of the balance between curability and physical properties of the cured resin. The blending amount of the (C) curing agent may be 0.1 mass % or more and 1.5 mass % or less, or 0.2 mass % or more and 1.0 mass % or less, based on the total amount of the paste composition.

[0058] [(D) Solvent] The (D) solvent used in the present disclosure is not particularly limited, but from the viewpoint of reducing thermal resistance, the (D) solvent may include a solvent having a solubility parameter (SP value) of 11 or more, or may include a solvent having a solubility parameter of 11 or more and 14 or less. The solubility parameter (SP value) is a value defined by the regular solution theory introduced by Hildebrand, and for example, the smaller the difference between the solubility parameters (SP values) of two components, the greater the solubility. When the (D) solvent contains a solvent having an SP value of 11 or more, the wettability of the interface is deteriorated, but the voids at the bonding interface are reduced, and the thermal resistance at the bonding interface is reduced. When the (D) solvent contains a solvent having an SP value within the above range, when a liquid flexible epoxy resin is used as the (B) thermosetting resin, the affinity between the liquid flexible epoxy resin and the (D) solvent is reduced because the SP value of the liquid flexible epoxy resin is in the range of 8 or more and less than 11, and the (D) solvent is less likely to remain in the system, so that the generation of voids is controlled and the thermal resistance is reduced. Furthermore, from the viewpoint of controlling voids and reducing thermal resistance, the difference in SP value between the (B) thermosetting resin and the (D) solvent may be greater than 2. The reason why the thermal resistance of the bonding interface is reduced when the (D) solvent contains a solvent having an SP value within the above range is presumably because the solvent has a high surface energy, which improves the bond to the (A) silver particles and the bonding interface. It is presumed that the larger the SP value, the more energetically unstable the interface becomes, and the higher the energy state acts effectively on the interface.

[0059] Examples of solvents with a solubility parameter of 11 or more include ethylene glycol monomethyl ether (δ=11.4), 1-butanol (δ=11.4), 2-propanol (δ=11.5), acetonitrile (δ=11.9), dimethyl sulfoxide (δ=12.0), dimethylformamide (δ=12.1), ethanol (δ=12.7), phenoxyethanol (δ=11.8), benzyl alcohol (δ=12.8), 1,6-cyclohexanedimethanol (δ=13.83), and ethylene glycol (δ=14.2). The solubility parameters of such solvents are disclosed, for example, in "AFMBurton, Chemical Reviews, 1975, Vol. 75, No. 6, p731-753". The (D) solvent may be phenoxyethanol, benzyl alcohol, 1,6-cyclohexanedimethanol, or ethylene glycol.

[0060] In the present disclosure, these exemplified solvents may be used alone or in combination of two or more. In order to reduce voids at the bonding interface and reduce thermal resistance, it is sufficient that the SP value of at least one solvent is within the above range, not the SP value of the mixed solvent. Examples of the (D) solvent other than the solvent whose SP value satisfies the above range include butyl carbitol (δ=8.5), propylene glycol diacetate (δ=9.6), dipropylene glycol methyl-n-propyl ether (δ=8.0), dipropylene glycol methyl ether acetate (δ=8.7), 1,4-butanediol diacetate (δ=9.6), 1,3-butylene glycol diacetate (δ=9.5), 1,6-hexanediol diacetate (δ=9.5), diethylene glycol monoethyl ether (δ=10.9), dipropylene glycol n-propyl ether (δ=9.5), dipropylene glycol n-butyl ether (δ=9.4), tripropylene glycol methyl ether (δ=9.4), tripropylene glycol n-butyl ether (δ=9.3), and the like.

[0061] Furthermore, from the viewpoint of reducing silver oxide on the surfaces of the silver particles and improving the sinterability of the silver particles, the (D) solvent may contain a primary alcohol having a flash point of 90° C. or higher in addition to having an SP value within the above range. When the (D) solvent contains the primary alcohol, the content thereof may be 5% by mass or more and 50% by mass or less, or may be 10% by mass or more and 40% by mass or less.

[0062] The content of the (D) solvent may be 0.5 mass % or more and 8.5 mass % or less, or may be 2.0 mass % or more and 8.0 mass % or less, based on the total amount of the paste composition, from the viewpoint of the coatability of the paste composition and void control.

[0063] In addition to the above components, the paste composition of the present disclosure may contain, as necessary, various additives that are generally blended in this type of composition, such as a curing accelerator, a stress reducing agent such as rubber or silicone, a coupling agent, an antifoaming agent, a surfactant, a colorant such as a pigment or dye, a polymerization initiator, various polymerization inhibitors, an antioxidant, and other additives. Each of these additives may be used alone or in combination of two or more.

[0064] In the paste composition of the present disclosure, the total content of the (A) silver particles, the (B) thermosetting resin, the (C) curing agent, and the (D) solvent may be 80 mass% or more, 90 mass% or more, or 95 mass% or more.

[0065] The paste composition of the present disclosure can be prepared by thoroughly mixing the above-mentioned (A) silver particles, (B) thermosetting resin, (C) curing agent, (D) solvent, and various additives that may be contained as necessary, followed by kneading using a disperse, kneader, triple roll mill, or the like, and then degassing.

[0066] The thermal conductivity of a cured product of the paste composition of the present disclosure may be 30 W / m·K or more, or may be 35 W / m·K or more. The thermal conductivity can be measured by the method described in the Examples.

[0067] The thermal resistance of a cured product of the paste composition of the present disclosure may be 0.4 K / W or less, or may be 0.3 K / W or less. The thermal resistance can be measured by the method described in the Examples.

[0068] The paste composition of the present disclosure has good adhesive properties, low thermal resistance at the bonding interface, and can give a cured product with excellent thermal conductivity and electrical conductivity, and therefore can be used as a die attach material for bonding elements, a material for bonding heat dissipation components, etc.

[0069] <Semiconductor device> The semiconductor device of the present disclosure has a semiconductor element and a substrate bonded together via a die attach material made of the above-mentioned paste composition, and therefore has excellent reliability.

[0070] The semiconductor element may be a known semiconductor element, such as a transistor or a diode. The semiconductor element may further include a light-emitting element such as an LED. The type of the light-emitting element is not particularly limited, and may include, for example, a light-emitting layer formed of a nitride semiconductor such as InN, AlN, GaN, InGaN, AlGaN, or InGaAlN on a substrate by the MOBVC method or the like. Examples of the element support member include support members made of materials such as copper, silver-plated copper, PPF (preplating lead frame), glass epoxy, and ceramics. EXAMPLES

[0071] The present disclosure will now be described in detail with reference to examples, but the present disclosure is not limited to these examples in any way.

[0072] (Production of silver particles) [Synthesis Example 1] 40 g of silver nitrate was dissolved in 10 L of ion-exchanged water to prepare a silver nitrate aqueous solution, to which 203 mL of ammonia water with a concentration of 26% by mass was added and stirred to obtain a silver ammine complex aqueous solution. The solution was brought to a liquid temperature of 10°C, and 28 mL of a 20% by mass aqueous solution of hydrazine monohydrate was dropped over 60 seconds while stirring to precipitate silver particles, thereby obtaining a silver particle-containing slurry. 1% by mass of oleic acid relative to the amount of silver was added to the slurry and stirred for 10 minutes. The slurry was filtered, and the residue was washed with water and methanol, and dried at 60°C in a vacuum atmosphere for 24 hours, resulting in an average particle size of primary particles: 20 nm, an average particle size of secondary aggregate particles: 1.1 μm, and a tap density of 5.2 g / cm. 3 , Specific surface area: 1.2m 2 / g, and the amount of oleic acid attached was 2.1 mass %. The silver particles obtained were confirmed to have a porosity of 25% as measured by the method described below, a void of 25% in the center, and a shell thickness of 0.275 μm. After sintering at 190° C. for 2 hours, the silver particles had a porosity of 43%, a shell thickness of 0.189 μm, and the change in shell thickness due to sintering was 31%.

[0073] [Synthesis Example 2] 50 g of silver nitrate was dissolved in 0.5 L of ion-exchanged water to prepare an aqueous solution of silver nitrate, to which 0.5 L of ammonia water with a concentration of 26% by mass was added and stirred to obtain an aqueous solution of silver ammine complex. The solution was brought to a liquid temperature of 10°C, and 1 L of an aqueous solution of sodium borohydride was added while stirring. (35 g of sodium borohydride was dissolved in 1 L of ion-exchanged water) to precipitate silver particles, and a silver particle-containing slurry was obtained. 1% by mass of oleic acid relative to the amount of silver was added to this slurry and stirred for 10 minutes. This slurry was filtered, and the residue was washed with water and methanol, and dried at 60°C in a vacuum atmosphere for 24 hours, resulting in an average particle size of primary particles: 200 nm, an average particle size of secondary aggregate particles: 5.0 μm, and a tap density of 0.75 g / cm. 3 , Specific surface area: 2.0m 2 / g, and the amount of oleic acid attached: 0.5 mass % silver particles were obtained.

[0074] [Examples 1 to 6, Comparative Examples 1 and 2] The components were mixed according to the formulation in Table 1 and kneaded in a three-roll mill to obtain a paste composition. The obtained paste composition was evaluated by the methods described below. The results are shown in Table 1. The materials used in the examples and comparative examples and shown in Table 1 are as follows.

[0075] [(A) Silver particles] (A1) Silver particles 1: Silver particles of Synthesis Example 1 (average particle size of primary particles: 20 nm, average particle size of secondary aggregate particles: 1.1 μm, porosity: 25%, shell thickness: 0.27 μm, maximum linear expansion coefficient: +5.5 ppm / °C, tap density: 5.2 g / cm 3 , Specific surface area: 1.2m 2 / g) (A2) Silver particles 2: Silver particles of Synthesis Example 2 (average particle size of primary particles: 200 nm, average particle size of secondary aggregate particles: 5.0 μm, porosity: 0%, maximum linear expansion coefficient: −0.6 ppm / ° C., tap density: 0.75 g / cm 3 , Specific surface area: 2.0m 2 / g) Silver particles 3: DOWA Ag nano powder (product name, manufactured by DOWA Electronics Co., Ltd., average particle size: 20 nm, porosity: 0%, maximum linear expansion coefficient: -0.1 ppm / ℃) Silver particle 4: TC-505C (product name, manufactured by Tokuriki Honten Co., Ltd., average particle size: 1.93 μm, porosity: 0%, maximum thermal expansion coefficient: -0.1 ppm / °C, tap density: 6.25 g / cm 3 , Specific surface area: 0.65m 2 / g)

[0076] [(B) Thermosetting resin] Flexible epoxy resin 1: YX7105 (trade name, manufactured by Mitsubishi Chemical Corporation, elastic modulus at 25°C: 0.033 GPa, epoxy equivalent: 480, SP value: 9.4) Flexible epoxy resin 2: YX7110 (trade name, manufactured by Mitsubishi Chemical Corporation, elastic modulus at 25°C: 0.028 GPa, epoxy equivalent: 1100, SP value: 9.4) Epoxy resin 1: YL980 (product name, manufactured by Mitsubishi Chemical Corporation, elastic modulus at 25°C: 2.5 GPa, epoxy equivalent: 190, SP value: 9.8)

[0077] The elastic modulus of the thermosetting resin (B) at 25°C is Epoxy before curing DETA was mixed into the resin in a stoichiometric amount, cured at 200°C for 2 hours, and cut into samples measuring 55 mm in length, 1 cm in width, and 20 μm in thickness. The samples were measured using a thermomechanical analyzer (Seiko Instruments Inc., device name: DMA) by raising the temperature from -50°C to 300°C at 10°C per minute.

[0078] [(C) Hardener] (C1) Phenolic resin: Bisphenol F (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) (C2) Dicyandiamide: DICY-7 (product name, manufactured by Japan Epoxy Resin Co., Ltd.)

[0079] [(D) Solvent] Solvent 1: HYSOLV EPH (product name, manufactured by Toho Chemical Industry Co., Ltd., SP value = 11.8, flash point: 135°C) Solvent 2: Butyl Carbitol (trade name, Kanto Chemical Co., Ltd., SP value = 8.5, flash point: 78°C) Solvent 3: Ethylene glycol (product name, Kanto Chemical Co., Ltd., SP value = 14.2, flash point: 111°C)

[0080] The SP value of the (B) thermosetting resin and the SP value of the (D) solvent are both values ​​disclosed in "AFMBurton, Chemical Reviews, 1975, Vol. 75, No. 6, pp. 731-753."

[0081] The (A) silver particles were evaluated by the following method.

[0082] [Average particle size of primary particles] The average particle size of the primary particles was measured as follows using Silver Particles 1 and Silver Particles 2 obtained in each of the Synthesis Examples above. Silver particles were embedded in Epoheat CLR (Buehler) at 60°C for 120 minutes. Cross-sectional milling was performed using an ion milling device (ArBlade5000, Hitachi High-Tech) at an acceleration voltage of 6 kV, processing mode C3 (±30°), and processing time of 30 minutes. The cross-sections of the obtained spherical silver particles were observed with a field emission scanning electron microscope (FE-SEM) (JEOL JSM-6700F) at an acceleration voltage of 1.0 kV and magnification of 10,000 to 200,000 times to measure the circle equivalent diameters of 200 silver particles. The circle equivalent diameters of the measured 200 silver particles were processed using image analysis software ImageJ (National Institutes of Health) and calculated by number averaging.

[0083] [Average particle size of secondary agglomerates] The average particle size of the secondary agglomerate particles of silver particles 1 and silver particles 2 was determined from the particle size at which the accumulated volume was 50% (50% particle size D50) in the particle size distribution measured using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, product name: SALAD-7500nano).

[0084] [Amount of organic protective molecules attached] The amount of attached organic protective molecules on silver particles 1 and silver particles 2 was measured by heating 20 mg of silver particles from 230°C to 320°C at a heating rate of 10°C / min in a nitrogen atmosphere using a thermogravimetry-differential thermal analyzer (TG-DTA) (manufactured by Seiko Instruments, product name: TG / DTA6200), measuring the amount of mass loss of the silver particles, and defining this value as the amount of attached organic protective molecules.

[0085] [Thermal expansion coefficient] The thermal expansion coefficients of Silver Particles 1 to 4 were measured according to the following procedure. A cylindrical pellet-shaped sample with a diameter of 5 mm and a thickness of 1 mm was obtained by applying a load of 200 kgf to the silver particles for 1 minute using a mini hydraulic press (Specac). The thermal expansion of the sample was measured using a thermomechanical analyzer (TMA) (Seiko Instruments Inc., product name: TMA SS150) under conditions of heating from room temperature (25°C) to 350°C at a heating rate of 20°C / min, and the thermal expansion coefficient was calculated based on the pellet length at 25°C. The maximum thermal expansion coefficient was determined as the thermal expansion coefficient that was maximum in the firing temperature range of 150 to 300°C.

[0086] [Tap Density] The tap densities of Silver Particles 1, 2, and 4 were measured according to the following procedure. Tap density (TD) was measured based on ASTM standard test method B 527 using a tap density measuring device (Tap-Pak Volumeter, Thermo Scientific) to measure the mass per unit volume of silver particles in a vibrated container (unit: g / cm 3 ) was measured.

[0087] [Specific surface area] The specific surface areas of silver particles 1, 2, and 4 were measured according to the following procedure. The specific surface area was measured by the BET single point method using nitrogen adsorption, using a specific surface area measuring device (Monosorb, manufactured by Quanta Chrome) after degassing at 60° C. for 10 minutes.

[0088] [Porosity] The porosity before and after sintering of silver particles 1 to 4 was measured according to the following procedure. Using silver particles, cross-sectional milling was performed in the same manner as in the evaluation method for the average particle size of primary particles to prepare a sample (sample 1) for measuring the porosity before sintering. Sample 1 was also sintered in a nitrogen atmosphere at 190°C for 2 hours to prepare a sample (sample 2) for measuring the porosity after sintering. The number of fields of view of the FE-SEM image of a field emission scanning electron microscope (FE-SEM) (JSM-6700F manufactured by JEOL) was set to 10 μm x 10 μm so that the cross sections of Samples 1 and 2 each contained 300 or more silver particles, and FE-SEM images were obtained. Next, the cross-sectional area of ​​the voids in the FE-SEM image of the silver particles and the total cross-sectional area of ​​the silver particles including the voids were measured using Mac-View (manufactured by Mountec), which is an image analysis type particle size distribution measurement software. Based on the measurement results, the cross-sectional area (μm 2 ) (total cross-sectional area of ​​the voids), and the cross-sectional area of ​​all silver particles in the field of view (μm 2 ) (total cross-sectional area) according to the following formula (1). Porosity (%) = total cross-sectional area of ​​pores / total cross-sectional area × 100 (1)

[0089] [Outer shell thickness of silver particles] The shell thickness before and after sintering of silver particles 1 was measured according to the following procedure. The shell thicknesses of 200 silver particles were measured from the FE-SEM images of Sample 1 and Sample 2 of Silver Particles 1 obtained in the above porosity measurement. The shell thickness of the silver particles was determined by taking the number-average of the shell thicknesses measured for the 200 silver particles.

[0090] [Change in shell thickness due to sintering] From the shell thickness before sintering and the shell thickness after sintering obtained by measuring the shell thickness of the silver particles, the rate of change in shell thickness due to sintering was calculated according to the following formula (2). Change in shell thickness due to sintering (%) = (T A -T B ) / T A×100 (2) (In the formula, T A is the shell thickness before sintering (μm), and T B is the shell thickness after sintering (μm).

[0091] The paste compositions obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were evaluated by the following methods.

[0092] [Cure shrinkage rate] The paste composition was applied to a copper substrate with a Ag-plated surface so that the paste film thickness after mounting was 30 μm, and then a gold-backed silicon chip with a gold-deposited layer on the bonding surface of 5 mm × 5 mm was mounted. This was cured at 190 ° C for 60 minutes to produce a semiconductor package. The film thickness (μm) after curing was measured with a micrometer (Mitutoyo, device name: MDC-25MX), and the cure shrinkage was calculated using the following formula. Curing shrinkage rate (%) = paste film thickness after curing / paste film thickness before curing × 100

[0093] [Thermal Conductivity] The paste composition was cured at 190° C. for 2 hours and cut into a sample measuring 1 cm long × 1 cm wide × 20 μm thick. The thermal conductivity of the obtained sample was measured by a laser flash method using a thermal conductivity meter (manufactured by Advance Riko Co., Ltd., device name: TC7000) in accordance with JIS R 1611:1997.

[0094] [Thermal resistance] The paste composition was applied to a copper substrate with an Ag-plated surface so that the paste film thickness after mounting was 30 μm, and then a thermal resistance TEG chip with a gold vapor deposition layer on the bonding surface of 5 mm x 5 mm was mounted, and the resulting semiconductor package was cured at 190°C for 60 minutes. The thermal resistance of the bonding part of the obtained semiconductor package was measured at room temperature (25°C) using a thermal resistance measuring device "T3ster" (Mentor Graphics).

[0095] [Volume resistivity] The paste composition was applied to a glass substrate (thickness 1 mm) by screen printing to a thickness of 30 μm, and cured for 60 minutes at 190° C. The volume resistivity of the resulting wiring was measured by the four-terminal method using a resistivity meter (product name "MCP-T600", manufactured by Mitsubishi Chemical Corporation).

[0096] [Adhesive strength] The paste composition was applied to a PPF (Ni-Pd / Au-plated copper frame) so that the paste film thickness after mounting was 30 μm, and then a 2 mm × 2 mm silicon chip was mounted and cured for 60 minutes at 190 ° C. After curing, the hot die shear strength was measured at room temperature (25 ° C) and 260 ° C. using a mount strength measuring device (4000Plus Bond Tester, Nordson).

[0097] [Reliability] The paste composition was applied to a copper frame with Ag plating on the surface so that the paste film thickness after mounting was 30 μm, and then a gold-backed silicon chip with a gold deposition layer on the bonding surface of 8 mm × 8 mm was mounted, and heat curing was performed at 190 ° C. for 60 minutes. The obtained sample was subjected to a thermal cycle treatment in a thermal cycle tester (2000 cycles of heating from -55 ° C. to 150 ° C. and then cooling to -55 ° C.). After the thermal cycle treatment, the presence or absence of peeling of the chip of the sample was observed with an ultrasonic microscope (FineSAT II, ​​manufactured by Hitachi Power Solutions Co., Ltd.) (number of samples = 5).

[0098] [Table 1]

[0099] The paste compositions of Examples 1 to 6, which satisfy the cure shrinkage rate of 15% or less, all have good adhesive properties, and the thermal resistance of the cured product is low at 0.4 K / W or less, and they have excellent thermal and electrical conductivity. In addition, semiconductor devices with excellent reliability can be obtained. [Explanation of symbols]

[0100] 10 Silver particles (secondary agglomerated particles) 1. Outer shell 2 void 3 Inside the shell 4. Outside the shell

Claims

1. (A) silver particles, (B) a thermosetting resin, (C) a curing agent, and (D) a solvent; A paste composition having a shrinkage rate of 15% or less after curing, the (A) silver particles comprise at least one type selected from: (A1) silver particles which are secondary agglomerate particles having an average particle diameter of 0.5 μm or more and 2.0 μm or less, which are formed by agglomeration of particles including primary particles with an average particle diameter of 10 nm or more and 100 nm or less, and which have an outer shell formed by particles including the agglomerated primary particles and voids present inside the outer shell; and (A2) silver particles which are secondary agglomerate particles having an average particle diameter of more than 2.0 μm and not more than 15.0 μm, which are formed by agglomeration of particles including primary particles with an average particle diameter of more than 100 nm and not more than 500 nm, the total amount of (A1) and (A2) in the silver particles is 40% by mass or more and 100% by mass or less, the (B) thermosetting resin is an epoxy resin having an epoxy equivalent of 200 or more and 2000 or less and an elastic modulus after curing of 0.033 GPa or less (wherein the elastic modulus is measured by mixing DETA with an epoxy resin before curing so as to obtain a stoichiometric amount, curing the resulting mixture at 200°C for 2 hours, cutting the resulting mixture into a sample having a size of 55 mm length x 1 cm width x 20 µm thickness, and raising the temperature of the sample from -50°C to 300°C at 10°C per minute using a thermomechanical analyzer (manufactured by Seiko Instruments Inc., device name: DMA)), in an amount of 1% by mass or more and 20% by mass or less relative to the composition; a paste composition in which the (C) curing agent contains a (C1) phenol resin and a (C2) dicyandiamide, the blending amount of the (C1) component is 1 part by mass or more and 10 parts by mass or less and the blending amount of the (C2) component is 0.5 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the (B) thermosetting resin, and the mass ratio of the (C1) component to the (C2) component [(C1):(C2)] is 1:1 to 10:

1.

2. 2. The paste composition according to claim 1, wherein the (A1) silver particles have a porosity, as defined by the following formula (1), of 20% or more and 50% or less before sintering, and a porosity of 30% or more and 60% or less after sintering under sintering conditions of a nitrogen atmosphere, a sintering temperature of 175 to 225°C, and a sintering time of 1 to 3 hours, and a rate of change in outer shell thickness due to sintering, as defined by the following formula (2), of 15% or more and 50% or less. Porosity (%) = total cross-sectional area of ​​pores / total cross-sectional area × 100 (1) (In the formula, the total cross-sectional area of ​​voids is the sum of the cross-sectional areas (μm2) of voids contained in all silver particles in a field of view when a cross-section of a silver particle (A1) cut with an ion milling device is observed with a field emission scanning electron microscope (FE-SEM), and the total cross-sectional area is the sum of the cross-sectional areas (μm2) of all silver particles in the same field of view.) Change in shell thickness due to sintering (%) = (TA - TB) / TA x 100 (2) (In the formula, TA is the shell thickness (μm) before sintering, and TB is the shell thickness (μm) after sintering under the above sintering conditions.)

3. 3. The paste composition according to claim 1, wherein the (A1) silver particles further have protective molecules attached thereto, and the amount of the protective molecules attached is 0.15 mass% or more and 3.0 mass% or less, based on the total amount of the (A1) silver particles.

4. 4. The paste composition according to claim 1, wherein the (A1) silver particles have a positive thermal expansion coefficient between 150 and 300° C. when thermal expansion is measured under conditions in which the temperature is increased from 25° C. to 350° C. at a heating rate of 20° C. / min.

5. 5. The paste composition according to claim 1, wherein the thermosetting resin (B) is a liquid flexible epoxy resin.

6. 6. The paste composition according to claim 1, wherein the (D) solvent contains a solvent having a solubility parameter (SP value) of 11 or more, and the content of the solvent is 0.5 mass % or more and 8.5 mass % or less with respect to the total amount of the paste composition.

7. A semiconductor device comprising a semiconductor element and a substrate bonded together via a die attach material comprising the paste composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Conductive resin paste and conductive resin membrane

    JP2003257244A

  • Silver powder and its manufacturing method

    JP2007270334A

  • Metal colloid particle, its paste and method for production thereof

    JP2010229544A

  • Thermosetting conductive paste composition

    JP2011100573A

  • Electroconductive resin composition, and semiconductor device using the same

    JP2012092201A